Health belief model in prevention of type II diabetes among high-risk individuals - Fateme Behesht aeen; Fateme Afrasiabi; Marzieh Kargar jahromi (International Journal of Public Health Science (IJPHS), 2022)
Objective: This descriptive study aimed to determine the diabetes prevention behaviors based on the health belief model among high-risk individuals.Methods: 220 randomly selected patients at risk of type II diabetes completed a 65-item questionnaire based on the constructs of the health belief model. Data analyzed by SPSS.Results: The mean score of knowledge among responders was 5.54+2.60, which indicated that 50.36% of the participants had gained the maximum score of knowledge. The results indicated that the constructs of the health belief model determined 19% of the variance in type II diabetes prevention behaviors.  Perceived barriers, perceived self-efficacy, and knowledge were the significant positive predictors of diabetes prevention behaviors. Based on the results, single respondents had higher knowledge levels, higher perceived severity, and lower perceived barriers compared to married ones. In addition, a significant relationship was observed between age, economic status, and education level and some constructs of the health belief model.Conclusion: The results indicated that the high-risk patients obtained moderate mean scores in type II diabetes prevention behaviors. These results could help improve educational programs with regard to beliefs, attitudes, and behaviors in order to promote type II diabetes prevention and self-care behaviors among at-risk populations, eventually enhancing their quality of life.